The relationship between personality and decision-making: a systematic literature review - Mendes, Fabiana Freitas; Mendes, Emilia; Salleh, Norsaremah (Elsevier B.V., 2019)
Context From a point of view, software development is a set of decisions that need to be made while the software is developed. Many alternatives should be considered, such as the technology to employ, or the most important features to implement. However, many factors can influence one’s decision-making, such as the decision maker’s personality.